Effectiveness of Warm Water Foot Soak and Benson Relaxation Techniques Combination in Reducing Blood Pressure of Hypertensive Patients - Imam Cahyo Murwidi; Fadila Abdullah (Universitas Muhammadiyah Palu, 2020)
Hypertension is called a silent killer because of its uncertain symptom. Therefore, early detection efforts are needed such as regular blood pressure check and effective management. This study aimed to determine the effectiveness of warm water foot soak and Benson relaxation techniques combination in reducing blood pressure as a medical treatment to the hypertension patients. This was a quasi-experiment study with one group pre and post-test design. The sample number of the study was 30 primary hypertension patients of Gambesi Community Health Centre of Ternate City working area. The result showed that there was a significant difference between pre (162.53±16.90mmHg) and post (154.33±19.06mmHg) systolic blood pressure mean, p-value was 0.000, systolic blood pressure mean at first 30 minutes after post-test was 146.00±18.49 mmHg (p=0.000), second 30 minutes was 139.93±15.98 mmHg (p=0.000), third 30 minutes was 136.33±14.06 mmHg (p=0.000) and fourth 30 minutes was 133.47±14.59 (p=0.000). There was a significant difference between pre (95.10±9.65mmHg) and post (90.00±9.47mmHg) diastolic blood pressure mean, p-value was 0.003, post diastolic blood pressure mean at first 30 minutes was 86.00±7.70 mmHg (p=0.000), second 30 minutes was 86.73±7.06 mmHg (p=0.000), third 30 minutes was 84.40±5.64 mmHg (p=0.000) and fourth 30 minutes was 83.47±5.38 (p=0.000). It could be concluded that combination of warm water foot soak and Benson relaxation techniques is effective to reduce blood pressure of hypertensive patient.